Hair Loss after Varicella Zoster Virus Infection - Hayderi, Lara El (S. Karger AG, 2013)
Varicella zoster virus (VZV) cutaneous infection occurs predominantly in epidermal and infundibular keratinocytes and accessorily in dermal dendritic cells. These latter cells play a role in cicatricial processes. Two patients are presented with localized alopecia after VZV infection. A 4-year-old girl presented localized hair loss affecting about 20% of her upper right eyelash immediately following the resolution of the varicella skin lesions. No regrowth was observed after 3 months. An 80-year-old woman with a prior history of localized alopecia areata of the left occipital area presented severe left herpes zoster affecting the V1 and V2 dermatomes. At precisely the same site of the previous episode, a localized plaque of alopecia areata recurred. After topical corticosteroid therapy, a progressive hair regrowth occurred after about 3 months. These case reports are the first relating cutaneous VZV infection as the origin for permanent cicatricial alopecia and transitory alopecia areata. Localized hair loss should be added to the cutaneous complications of VZV skin infection.